2008
DOI: 10.1007/s10295-008-0327-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of lignocellulosic biomass: biochemical and molecular perspectives

Abstract: In view of rising prices of crude oil due to increasing fuel demands, the need for alternative sources of bioenergy is expected to increase sharply in the coming years. Among potential alternative bioenergy resources, lignocellulosics have been identified as the prime source of biofuels and other value-added products. Lignocelluloses as agricultural, industrial and forest residuals account for the majority of the total biomass present in the world. To initiate the production of industrially important products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
544
1
59

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,053 publications
(606 citation statements)
references
References 114 publications
2
544
1
59
Order By: Relevance
“…The biopreparation did not differ in terms of nonspecific cellulolytic activity from commercially available enzyme preparations, which could potentially be used for organic biomass pretreatment prior to anaerobic bioconversion. Kowalska-Wentel (2015) or Pectinex Ultra SP-L (Novozyme, Bagsvaerd, Denmark β-galactosidase activity immobilized onto Eupergit C) from Aspergillus aculeatus (Aslan and Tanrıseven, 2007). The enzyme mixture was characterized by the presence of other enzymes with relatively wider range and high activity, which is its advantage over others biopreparations mentioned above.…”
Section: The Characteristics Of the Biopreparationmentioning
confidence: 99%
“…The biopreparation did not differ in terms of nonspecific cellulolytic activity from commercially available enzyme preparations, which could potentially be used for organic biomass pretreatment prior to anaerobic bioconversion. Kowalska-Wentel (2015) or Pectinex Ultra SP-L (Novozyme, Bagsvaerd, Denmark β-galactosidase activity immobilized onto Eupergit C) from Aspergillus aculeatus (Aslan and Tanrıseven, 2007). The enzyme mixture was characterized by the presence of other enzymes with relatively wider range and high activity, which is its advantage over others biopreparations mentioned above.…”
Section: The Characteristics Of the Biopreparationmentioning
confidence: 99%
“…Total weight loss of rice straw included the degradation of cellulosic materials and non-cellulosic materials. In plant tissue, in addition to cellulose, hemicellulose, lignin, there are a lot of other material such as ash, pectin, protein and other components which occupy a considerable proportion (about 30%) [2]. Figure.2 showed that there was still about 30% undegraded material in rice straw at the end of the fermentation; main ingredient was 80% ash, which is hard to biotransformation but can be effectively utilized.…”
Section: Stability Of Microbial Consortium Lzf-12mentioning
confidence: 99%
“…With the depletion of non-renewable energy, as the most attractive and promising avenue for cost-efficient treatment, bioconversion of large amounts of lignocellulosic biomass into fermentable material has been considered to be potential application in the area of bioenergy generation [2]. Therefore, enormous research efforts have been invested on bioconversion of lignocellulosic biomass in decades [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Pada bakteri misalnya, enzim ini terdapat dalam komplek multi enzim yang disebut selulosom dan terdiri dari beberapa subunit. Sedangkan selulase dari Trichoderma reesei mengandung dua eksoglukanase, paling sedikit empat endoglukanase dan satu β-glukosidase (Kumar et al, 2008).…”
Section: Pendahuluanunclassified